Assessment of a terrestrial protected area for the conservation of freshwater biodiversity - Nogueira, Joana Garrido (2018)
Freshwater ecosystems are essential to human well-being and most have high biodiversity. However, this biodiversity has been suffering severe declines owing to the expansion of human activities. Protected areas (PAs) are essential for biodiversity conservation and have proved to be successful in stopping species extirpation if managed properly. Unfortunately, they are usually focused on terrestrial biodiversity, leaving freshwater ecosystems aside. The main goal of this study was to determine the influence of a PA (Montesinho Natural Park (MNP), Portugal) on freshwater biodiversity. Aquatic macroinvertebrates and fishes were surveyed, and biodiversity (richness, abundance, Shannon-Wiener diversity, and Pielou's evenness) and water quality (IASPT) indices were calculated inside, at the periphery and outside the MNP. Results showed that the PA does not affect positively either water quality or the two faunal groups monitored. Macroinvertebrate communities were not influenced by the PA; however, the abundance of pearl mussel Margaritifera margaritifera was significantly higher and size was significantly lower inside the MNP. The richness and abundance of fish communities were significantly higher outside the MNP, except for trout Salmo trutta abundance which was higher inside the MNP. Given these results, the MNP does not guarantee the safeguard of overall aquatic biodiversity and habitats and we propose an extension of MNP to downstream areas in order to increase the number of species (mostly cyprinids) under legal protection. This work demonstrates that terrestrial PA planning and management should also consider aquatic biodiversity to achieve successful conservation.